(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Immune system studied in 36 patients with chronic pancreatitis (CP) and 36 healthy individuals. In patients with CP showed a deficit of T-lymphocytes and its subpopulations voltage humoral immunity and cytokine profile. Using thymoptinum (dose 0.8-1.0 mg per course) in combined with conventional trea-tment in patients with CP led to an increase in cellular immunity and stabilization of cytokine levels.